Ein Messplatz für Sportspielentscheidungen - Raab, M.; Gärtner, K.; Kapaun, M. (Leipziger Sportwissenschaftliche Beiträge, 2007)
About 80 measuring stations used by top athletes are run in Germany today. They have two main criteria in common. Firstly, they all support diagnostics of a sportspecific technical training. Secondly, the development of each measuring station and its corresponding training structure is rather based on practical knowledge than on scientific theory. The conception of MotionLab is expected to implement above all the diagnosis of performances in top athletes. In addition, theorybased developments and quality tests are to establish modules for the use of different field games and performance levels. Using examples of MotionLab test runs in top and junior elite sports in handball the procedures are exemplarily described.